Rozovia, a replacement name for Nordia Rozova, 1968 (Trilobita) non Jairajpuri and Siddiqi, 1964 (Nematoda), preoccupied - Doweld, Alexander B. (Zootaxa, 2015)
The generic name Nordia (N. lepida Rozova, 1968, by original designation) was proposed by Rozova (1968: 108) for a new trilobite genus from the Upper Cambrian of the Tajmyr peninsula (NW Siberia, Krasnojarsk territory, Russian Federation). However, this name was preoccupied by Nordia Jairajpuri and Siddiqi (1964: 2) which is served as a type for a family Nordiidae Jairajpuri & Siddiqi and subfamily Nordiinae Jairajpuri & Siddiqi (Nematoda: Dorylaimida) (Vinciguerra, 2006). To resolve homonymy, in accordance with the article 60 of the International Code of Zoological Nomenclature, Rozovia nom. nov. (type species Nordia lepida Rozova, 1968; Rozovia lepida (Rozova) comb. nov.) is here proposed as a replacement name for Nordia Rozova non Jairajpuri and Siddiqi to honor Antonina Viktorovna Rozova, eminent Russian palaeontologist (Trilobita) and stratigrapher of Siberia.